2008
DOI: 10.1063/1.2837249
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability dependence on the stacking order and thickness ratio of the CoPt–TiO2∕CoCrPt–SiO2 stacked media

Abstract: Thermal stability of the present CoCrPt–SiO2 media becomes a more critical issue as recording density steadily increases. In the present study, thermal stability of the stacked media composed of high Ku CoPt–TiO2 and normal Ku CoCrPt–SiO2 was studied by changing stacking order and thickness of each layer while keeping a constant total thickness. When the CoPt–TiO2 layer was placed under the CoCrPt–SiO2 layer, negative nucleation field and coercivity increased much more than those of the reverse stacking case. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For simplicity, they are assumed to be the same value. Uniaxial crystalline anisotropy of the soft magnet K U,t is varied from 0 to 5.0 × 10 5 J m −3 and that of the hard magnet is fixed to K U,b = 5.0 × 10 5 J m −3 , respectively [6,9]. Intragranular exchange constant A = 1×10 −11 J m −3 , intergranular exchange constant A int.exch is 2% of A, which corresponds to the intergranular exchange coupling strength J = 2 mJ m −2 , and the wetting angle ϕ is equally varied from 90 • to 150 • for the soft and hard materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For simplicity, they are assumed to be the same value. Uniaxial crystalline anisotropy of the soft magnet K U,t is varied from 0 to 5.0 × 10 5 J m −3 and that of the hard magnet is fixed to K U,b = 5.0 × 10 5 J m −3 , respectively [6,9]. Intragranular exchange constant A = 1×10 −11 J m −3 , intergranular exchange constant A int.exch is 2% of A, which corresponds to the intergranular exchange coupling strength J = 2 mJ m −2 , and the wetting angle ϕ is equally varied from 90 • to 150 • for the soft and hard materials.…”
Section: Resultsmentioning
confidence: 99%
“…In experimentally fabricated stacked structures, there are inconsistencies in oppositely stacked structures. In [6,7], it is reported that the stacked layer has higher coercivities than a single hard layer, and in some cases the bottom layer is magnetically harder than the upper layer or its saturation magnetization is smaller than the upper layer. The authors of [6] studied the behaviour as a viewpoint of the lattice distortion due to the contact of materials which have different lattice parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation